Fikih Hak Asasi Manusia Menguak Kejahatan Tindak Pidana Korporasi Trafficking - Miftahul ulum (STAI Syaichona Moh. Cholil Bangkalan, 2018)
This paper discusses the corporate crime of human trafficking. The background used is the assessment that classifies Indonesia in third place for the handling of human trafficking by the international community. The word â€œHero Exchangeâ€ may often be heard, they are the workers from Indonesia who often become victims of Human Trafficking, victims sometimes traded not only for the purpose of prostitution or other forms of sexual exploitation, but also includes other forms of exploitation, such as forced labor or services, slavery or practices similar to slavery. Various government policies are made concerning the protection of women and children, basically made â€‹â€‹relatively comprehensive policies, ranging from Basic Act 1945 and the rules below. However many government policies in tackling this problem is not followed by real action in the field and it can be concluded, the legal protection of women and children victims of human trafficking is still felt less effective. This is evident from the very rarity of severe criminal imposed by the judge against traffickers. The absence of compensation in the form of sanctions against traffickers also add to the sense of injustice padakorban trafficking who have suffered both physically, mentally, and economically.